Service quality, customer satisfaction and corporate image as a key activator of store loyalty in traditional trade - Veloso, Cláudia M. (2020)
Currently one of the main challenges for managers in the retail industry is to provide and maintain customer satisfaction. While the reasons for an initial purchase in a retail store may be due to factors partially outside the control of retail managers, the ability to create a satisfactory experience for the consumer remains, to a considerable degree, in the hands of both the management and the retail staff. It is crucial for managers of traditional retail stores to have a good and clear understanding of exactly what customers are wishing to obtain. The main purpose of this research is to identify the dimensions of service quality and examining the interrelationships among customer satisfaction, image and customer loyalty and service quality in the traditional retail. A multi-level and hierarchical model is used as a framework to synthesize the impacts of customer satisfaction, service quality and corporate image on loyalty of customers in the traditional retail. The results revealed that service quality is the main determinant of customer satisfaction and corporate image. Also corporate image significantly influences customer satisfaction. Furthermore, customer satisfaction, corporate image and service quality significantly affect customer loyalty. This research is of particular significance to the literature in retail and to practitioners as well, since there are few studies in this field applied to the Portuguese traditional retail market.